PENGARUH KOMITMEN OGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KABUPATEN SIJUNJUNG (2016) - Iljasmadi, Iljasmadi (Jurnal Manajemen Pendidikan, 2019)
The problem raised in this study was the performance of the Sijunjung District Office of Manpower and Transmigration Staff, the research variables were organizational commitment, job satisfaction and employee performance. This study aims to reveal (1) the effect of organizational commitment on employee performance, (2) the effect of job satisfaction on employee performance, (3) the influence of organizational commitment and job satisfaction together on employee performance. Based on observations and studies of experience, the researchers found that the performance of the staff of the Sijunjung District Office of Manpower and Transmigration was still relatively low. Then the data were analyzed using correlation and regression techniques with the help of the SPSS for Windows version 13.00 computer program. The results of the analysis show that there is a contribution of organizational commitment to employee performance 78.2% and contribution to job satisfaction on employee performance 58%. While the contribution of organizational commitment and job satisfaction simultaneously on employee performance is 74.2%. If you look at the effect on the regression equation Y = 22,499 + 0,590 X1 + 0,212 X2. Based on the results of these studies, the researchers concluded that there was a significant effect of organizational commitment and job satisfaction together on employee performance. So the authors suggest to the parties concerned to agree and keep the commitments that have been made with employees, so that employee performance is better or significantly improved.